2017
DOI: 10.4172/2572-4983.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Level among School Children with Atopic Dermatitis

Abstract: Background: Atopic dermatitis (AD) is a chronic inflammatory skin condition. The pathogenesis of AD is still not fully understood. The association between obesity and AD suggests a potential role for adipocytes hormones, mainly leptin, which had variable immunological functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These results were consistent with those of a case-control study conducted in Egypt, which revealed that the serum leptin level was significantly elevated among cases than healthy controls. 17 In contrast, a study conducted by Nagel et al revealed no significant associations between high leptin levels and the prevalence of the symptoms of atopic dermatitis. 18 On another hand, our study also showed that there is a significant association between high leptin level and high IgE level since 75.6% of the patients who had high leptin level also had a high IgE level.…”
Section: Discussionmentioning
confidence: 88%
“…These results were consistent with those of a case-control study conducted in Egypt, which revealed that the serum leptin level was significantly elevated among cases than healthy controls. 17 In contrast, a study conducted by Nagel et al revealed no significant associations between high leptin levels and the prevalence of the symptoms of atopic dermatitis. 18 On another hand, our study also showed that there is a significant association between high leptin level and high IgE level since 75.6% of the patients who had high leptin level also had a high IgE level.…”
Section: Discussionmentioning
confidence: 88%
“…High leptin levels were found by Kimata (2002,2006) in children with IgE-associated AD, especially in those with fatty liver [ 72 , 75 ]. Another study also showed high leptin in AD children, mainly in girls [ 81 ]. In addition, teenagers, and adults with AD, both with normal and high BMI had high leptin concentrations compared with controls [ 83 ].…”
Section: Role Of Leptin In Admentioning
confidence: 99%
“…Jaworek et al (2020) reported similar results, but leptin was not correlated with AD severity, sex, age or BMI [ 68 ]. By contrast, low leptin levels were significantly found in lactating adult women with AD compared with their healthy counterparts [ 81 ], as well as in AD children, in which leptin was inversely associated with the severity of AD [ 79 ]. Nonetheless, other studies did not show a relationship between this skin disease and leptin in neither children [ 74 ] nor teenagers and adults [ 77 ].…”
Section: Role Of Leptin In Admentioning
confidence: 99%
See 1 more Smart Citation